14th International Conference on Image Analysis and Processing (ICIAP 2007) 2007
DOI: 10.1109/iciap.2007.4362751
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Score Selection for Fusion of Multiple Biometric Matchers

Abstract: A biometric system for user authentication produces a matching score representing the degree of similarity of the input biometry with the set of templates for that user. If the score is greater than a prefixed threshold, then the user is accepted, otherwise the user is rejected. Typically the performance are evaluated in terms of the receiver operating characteristic (ROC) curve, and the equal error rate (EER). In order to increase the reliability of authentication through biometrics, the combination of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…It is easy to see that the distribution of the output values of the Ideal Score Selector allows a better separation between the classes with respect to each of the combined classifiers. It can be easily seen that the above Ideal Score Selector exhibits a better ROC curve than the ROC curves of each individual classifiers used in the combination, and consequently a larger AUC [14]. Moreover, it has also been shown that the Ideal Score Selector always attains a larger AUC than that obtained by the linear combination, whatever the value of the weights, and the number of classifiers [14].…”
Section: Classifier Selectionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is easy to see that the distribution of the output values of the Ideal Score Selector allows a better separation between the classes with respect to each of the combined classifiers. It can be easily seen that the above Ideal Score Selector exhibits a better ROC curve than the ROC curves of each individual classifiers used in the combination, and consequently a larger AUC [14]. Moreover, it has also been shown that the Ideal Score Selector always attains a larger AUC than that obtained by the linear combination, whatever the value of the weights, and the number of classifiers [14].…”
Section: Classifier Selectionmentioning
confidence: 89%
“…The "Ideal Score Selector", proposed in [14], represents the upper bound of the selection strategy. The output of such Ideal Score Selector can be computed as:…”
Section: Classifier Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we only mention the related works of score level fusion which is based on evolutionary technique like Pso, Ga, Aco and other optimization technique. Dynamic selection of matching score was proposed by Tronci et al [8] in which they show that the dynamic selection of matching score can provide a better performance than a unimodal system. Veeramachaneni et al [9] was proposed an adaptive multimodal biometric management algorithm which is based on the combination of PSO and Bayesian decision fusion.…”
Section: Related Workmentioning
confidence: 99%
“…Tronci et al [8] have recently investigated another aspect of multimodal problem that focused on the dynamic selection of matching scores from all the available matching scores. The best matching score from a set of matching scores was selected based on the likelihood of input user being genuine or impostor.…”
Section: Related Workmentioning
confidence: 99%